If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -15 = 45 Reorder the terms: -15 + -3y = 45 Solving -15 + -3y = 45 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -3y = 45 + 15 Combine like terms: -15 + 15 = 0 0 + -3y = 45 + 15 -3y = 45 + 15 Combine like terms: 45 + 15 = 60 -3y = 60 Divide each side by '-3'. y = -20 Simplifying y = -20
| 7x+3(x-2)=6(x+1)-3 | | 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 |